Pembelajaran Pendidikan Multikultural pada Program Studi Pendidikan Agama Islam - Hamna Sari Siregar (Fitrah: Journal of Islamic Education, 2022)
Islamic religious education teachers have an obligation to understand and understand multicultural education learning. This is due to the plurality of the Indonesian nation which has strong potential with this diversity, and also has the potential to be weak with this diversity. Of course a strong desire with diversity is a non-negotiable choice. Without mastering multicultural education it seems difficult to manage this diversity into an advantage. On that basis, this study aims to analyze the learning of multicultural education in Islamic religious education study programs, which focus on 3 things namely curriculum, learning strategies and learning evaluation. This research was conducted at STIT Gunung Tua Padang Lawas Utara. This study uses a type of qualitative research with a phenomenological study approach. Data collection techniques using observation, interviews and documentation studies. The results of the study show that the multicultural education curriculum contains tolerance, ethnoculture and culture, the dangers of anxiety, conflict resolution, democracy, plurality. The learning strategies are problem solving, cognitive moral development and role playing. Evaluation of multicultural learning uses fortopolio, behavioral observation, and attitude analysis.